Non-invasive urine testing of EGFR activating mutation and T790M resistance mutation in non-small cell lung cancer. Issue 1 (December 2015) - Berz, David; Raymond, Victoria; Garst, Jordan; Erlander, Mark
Abstract Background The increasing understanding of non-small cell lung cancer (NSCLC) biology over the last two decades has led to the identification of multiple molecular targets. This led to the development of multiple targeted therapies in the primary and secondary resistance setting and the epidermal growth factor receptor (EGFR ) gene remains the most frequently observed molecular target in NSCLC. Tissue biopsies remain the standard for the identification of suchEGFR mutations. Obtaining serial tissue biopsies, especially in the secondary resistance setting is associated with multiple medical and logistical challenges. Utilizing circulating tumor DNA (ctDNA) fragments for molecular analysis can overcome these challenges and aid in therapeutic decision-making. Case presentation Here we present a present a 72-year-old Korean woman with metastatic, EGFR L858R mutated bronchogenic adenocarcinoma. She developed skeletal progression on treatment with first and second generation tyrosine kinase inhibitors (TKIs). Repeated biopsies failed to provide informative molecular test results. A novel urine ctDNA assay was utilized and confirmed T790M positive status. The patient was started on a third generation TKI, which led to a measurable clinical response. Conclusions Utilization of urine liquid biopsies forEGFR diagnostics are feasible and provided critical clinical information in this patient's case. Urine liquid biopsy represents a viable alternative to tissue biopsy, particularly in the secondary resistance setting, when tissue is not available for molecular testing.